Understanding facilitators and barriers to COVID-19 vaccination in the Zimbabwean population: a qualitative analysis - Nicholas Midzi; Masceline Jenipher Mutsaka-Makuvaza; Lincoln Sunganai Charimari; Priscilla Mangwiro; Tonderai Manengureni; Gladys Mugadza (BMC, 2024)
Abstract Background Vaccines are effective biological interventions that reduce health burdens. However, during the COVID-19 pandemic, there were concerns about varying levels of COVID-19 vaccination coverage in the Zimbabwean population. This study aimed to understand facilitators and barriers to COVID-19 vaccine uptake in the Zimbabwean population. Methods In September-October 2023, key informant interviews (KIIs) and focus group discussions (FGDs) were conducted with a sample comprising health workers, village health workers, church leaders, traditional healers, teachers, youth leaders and the general population selected across the country. At each site, the participant sample was homogeneous. Data were collected using audiotapes, transcribed verbatim, and translated into English. Data were analysed manually using thematic analysis. Results Ten FGDs and 30 KIIs were conducted across the country. Among the facilitators of COVID-19 vaccine uptake were the perceived benefits of COVID-19 vaccination, such as protection from infection, severe disease and death. People also complied with COVID-19 vaccination because of the government's call for mandatory vaccination, travel restrictions, restrictions when entering some premises for services, visiting, working, learning and functions. Barriers to COVID-19 vaccine uptake included low-risk perception, negative attitudes emanating from concerns about the origins of the vaccines, COVID-19 cases or death of vaccinated people, negative peer influence, religious doctrines, cultural beliefs and misconceptions circulating through social media. Other barriers included knowledge gaps on COVID-19 vaccines, safety, effectiveness, side effects, access-related challenges to COVID-19 services and concerns over the changing policy on COVID-19 vaccination. Conclusions The study has shown the importance of community engagement and data-driven public health communication strategies to facilitate behaviour change for increased uptake of a vaccine. In future epidemics, public health campaigns should focus on the timely provision of information explaining the benefits of an intervention, addressing safety concerns more effectively. To build trust and hence improve vaccine uptake by the public, there is a need for continuous engagement with people and to provide platforms for dialogue to address issues contributing to low vaccine uptake.